Who switched off my brain? : controlling toxic thoughts and emotions - Leaf, Caroline, 1963- (Rivonia, South Africa : Switch On Your Brain, 2007)
Describes how negative thoughts affect brain processes, bodily functions, and overall physical health, along with ways to control negative thoughts and their consequences with positive thinking techniques.
"You can learn to control your thought life."
Includes bibliographical references.
Keywords: Healing -- Psychological aspects; Thought and thinking; Brain; Self-actualization (Psychology); Healing -- Psychological aspects; Brain; Healing -- Psychological aspects; Self-actualization (Psychology); Thought and thinking